Essays on spillover effects of economic and geopolitical uncertainty : a thesis submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Finance at Massey University, Auckland (Albany), New Zealand - Hasan, Mudassar (Massey University, 2020)
We are living in an age of uncertainty. While uncertainty can originate from multiple sources, the most prominent ones include economic policies and geopolitical conditions. Over the past two decades, geopolitical and economic policy uncertainties have risen dramatically around the globe, raising concerns among policymakers and financial market participants about the cross-country and cross-market transmission effects of these uncertainties. Consequently, a growing body of literature has emerged around the measurement of uncertainty, the cross-country transmission of uncertainty, and the spillover effects of a given uncertainty for financial markets. By offering several advantages over other measures of uncertainty, news-based uncertainty indicators have become increasingly popular since the seminal work by Baker, Bloom, and Davis (2016). As the transmission of geopolitical uncertainty across countries and that of economic policy uncertainty to financial markets carry important implications for risk-management and policy-making decisions, it is crucial to understand and explain the behavior of these transmission mechanisms. By relying on news-based indicators of geopolitical and economic policy uncertainty, this thesis contributes to the literature by exploring the potential determinants of uncertainty transmission to stock markets as well as across countries. The first essay estimates and explains the cross-country transmission of geopolitical uncertainty (GPU). Using the news-based GPU indices for a sample of emerging economies along with the United States, the spillover models are employed to measure the pairwise and system-wide transmission of GPU. A substantial amount of GPU transmission is found across the sample countries, with some countries and geographical clusters are being more prominent than others. A cross-sectional analysis, motivated by a gravity model framework, is further utilized to explain the pairwise transmission of GPU, which reveals that bilateral linkages and country-specific factors play an essential role in driving the transmission of GPU. The overall findings continue to hold even after considering the short- and long-term time horizons. The findings of this essay may help predict the trajectory of GPU from one country to another, which is an essential input for the assessment of cross-border investment appraisals as well as international stability initiatives. A bulk of the literature has examined the impact of US uncertainty on international stock markets without paying much attention to the correlation between the US and the other stock markets. Motivated by this void in the extant literature, the second essay examines the role of US uncertainty in driving the US stock market’s spillovers to global stock markets, after controlling for the stock market correlation. To this end, I consider a wide range of stock markets around the world, as well as three news-based uncertainties from the US, namely economic policy uncertainty (EPU), equity market uncertainty, and equity market volatility. I find that the US uncertainties significantly cause the spillovers from the US to global stock markets. This causality from US uncertainties depends upon certain country-characteristics. Specifically, the US uncertainties explain better the spillovers between US and target countries, when those countries have a higher degree of financial openness, trade linkage with the US, and vulnerable fiscal position. Improved levels of stock market development in the target countries, however, mitigate their stock markets’ vulnerability to the US uncertainty shocks. The essay offers potential insights and implications for investors and policymakers. Inspired by the concerns that small open economies may well be more vulnerable to foreign uncertainty than to local uncertainty, the third essay focuses on New Zealand, which is a small open economy. This essay introduces a weekly EPU index for New Zealand and, and examines the return and volatility spillovers from NZ EPU and US EPU on the aggregate (NZSE) and sectoral indices of New Zealand stock market. Overall, the findings suggest that NZ equity sectors and NZSE receive much stronger and more pronounced spillover effects from US EPU compared to the local counterpart. While the return spillovers from both EPUs are somewhat similar yet limited to just a few sectors, the volatility spillovers from US EPU on NZ sectors outstrip those from the NZ EPU. For volatility spillovers, the domestically oriented sectors are relatively more vulnerable to NZ EPU, while those having export/import concentration with the US are mainly susceptible to US EPU. The findings of this essay may be useful to investors seeking sectoral diversification opportunities across New Zealand and the US.
Listed in 2020 Dean's List of Exceptional Theses
Keywords: Stock exchanges; Uncertainty; Economic policy; Geopolitics; Dean's List of Exceptional Theses; 350202 Finance